IMPLEMENTASI KEBIJAKAN KEPEMUDAAN PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI SULAWESI - Wiarse, I Made (Katalogis, 2019)
The purpose of this study was to analyze the implementation of youth policy at the Department of Youth and Sports of Central Sulawesi Province. Research location at the Office of the Department of Youth and Sports of Central Sulawesi Province. The selection of informants using Purposive is the technique of determining informants with certain considerations by setting 5 informants. Data is collected through observation, interview, and documentation techniques. In this study researchers used the Milles Hubermen analysis approach technique. The results of the study are. 1. Communication, in policy implementation is very influential on the acceptance of policies by policy implementers and policy recipients, so that the quality of communication will influence in achieving the effectiveness of the implementation of the policy. In addition, based on indicators, namely transmission, clarity, consistency, it can be described that communication has proceeded well in supporting policy implementation by seeing meetings between policy implementers and policy recipients. 2. Resources, Resources are one of the variables that influence the success and failure of policy implementation such as human resources (staff), namely staff in inadequate categories. Budgetary resources (financial / financing, limited available funding causes constraints in a variety of appropriate and appropriate youth programs must be limited, funding in the category is inadequate, even though there has been information and no abuse of authority. Supporting facilities and infrastructure facilities in the category inadequate 3. Disposition by the Department of Youth and Sports of Central Sulawesi Province in the context of implementing policies based on observations and interviews shows that the disposition has proceeded as it should.4 The structure of the bureaucracy implemented in the implementation of the policy has been running well because of many influencing it works well like SOP and fragmentation.